Effect of extrusion conditions and lipoxygenase inactivation treatment on the physical and nutritional properties of corn/cowpea ( Vigna unguiculata ) blends - Sosa-Moguel, Odri (2009)
The influence of lipoxygenase inactivation and extrusion cooking on the physical and nutritional properties of corn/cowpea (Vigna unguiculata) blends was studied. Corn was blended in an 80:15 proportion with cowpea flour treated to inactivate lipoxygenase (CI) or non-inactivated cowpea flour (CNI). Extrusion variables were temperature (150°C, 165°C and 180°C) and moisture (15%, 17% and 19%). Based on their physical properties, the 165°C/15% corn:CNI, and 165°C/15% corn:CI, and 150°C/15% corn:CI blends were chosen for nutritional quality analysis. Extrudate chemical composition indicated high crude protein levels compared with standard corn-based products. With the exception of lysine, essential amino acids content in the three treatments met FAO requirements. Extrusion and lipoxygenase inactivation are promising options for developing corn/cowpea extruded snack products with good physical properties and nutritional quality.